Studies on nestling growth patterns of three bird species in Southern India - Thomas Nithiyanandam, G.; Asokan, S. (Scientific Journal of Zoology, 2015)
This paper reports the growth of nestlings of Indian Roller Coracias benghalensis, Common Myna Acridotheres tristis and Black Drongo Dicrurus macrocercus in Nagapattinam District of Tamil Nadu, India. The body of newly hatched nestlings was naked, fleshed colored and eyes closed. The newly hatched nestlings of the Indian Roller were 16.33 g in weight and reached maximum of 284.0 g on day 24. The weight of newly hatched Common Myna nestlings was 4.2 g and attained a maxim weight of 116.3 g on day 24. The newly hatched nestlings of the Black Drongo were 5.64 g in weight and reached maximum weight of 43.50 g on day 15. A reduction in weight was noticed in all the three species in the last few days of nestling period. The other body parts attained maximum maturity from hatching to fledging.